Surgical margins do not affect prognosis in high grade myxofibrosarcoma. Issue 7 (July 2016) - Sambri, A.; Bianchi, G.; Righi, A.; Ferrari, C.; Donati, D.
Abstract: Introduction: Myxofibrosarcoma (MFS) is one of the most common soft tissue sarcomas (STS) in elderly patients and it primarily affects the extremities. The aim of this retrospective analysis is to understand the natural history of MFS and whether adequate treatment influence prognosis. Patients and methods: We reviewed 129 adult patients with primary, localized, FNCLCC grade 3 MFS of the extremities operated at Istituto Ortopedico Rizzoli, Bologna. Sarcoma specific survival (SS), local recurrence (LR) and distant metastasis (DM) were analyzed. Results: Among excised MFS (119), 106 (89.9%) had R0 margins, 13 (10.1%) R1 margins. No significant correlation between margins adequacy and tumor depth, location and size was found. Estimated SS was 73.2% at 5 years and 66.3% at 10 years, with a better SS in superficial MFS (p = 0.011). Local recurred MFS had a worse SS (p = 0.049). Local recurrence-free rate was 74.3% at 5 and 10 years. Even if not significant, a better outcome in term of LR was observed in superficial MFS and R0 margins. Distant metastasis-free survival was 75.6% at 5 years and 72.9% at 10 years, with a better outcome in superficial MFS (p = 0.012). Discussion: Myxofibrosarcoma remain a debated entity with specific behavior features. Myxofibrosarcoma tends to local recur due to its infiltrative grow pattern making difficult to achieve "safe margins". To date, surgical margins as classified for other STS are not predictive of LR and patients' survival. Tumor grade and depth are still the most important prognostic factors.